Bangladesh public service commission : perceptions, problems and predictions - Jahan, Dr. Ferdous; Shahan, Asif Mohammad; Biswas, Niloy Ranjan (BRAC University, 2011)
Background paper for Institutions of Accountability: Public Service Commission.